HUBUNGAN KEBIASAAN MENYIKAT GIGI PADA ANAK KELAS V DENGAN PENYAKIT GINGIVITIS DI SEKOLAH DASAR - Irfan Nur Fajri Rahmat; Eliza Herijulianti; Ulfah Utami; Devy Octaviana (Poltekkes Kemenkes Bandung, 2023)
The most common dental and oral disease in children, apart from caries, is gingival inflammation (gingivitis). The high prevalence of gingivitis in Indonesia is due to the fact that people have not implemented good and effective habits in brushing their teeth. This study aims to determine the habit of brushing teeth, the frequency of students experiencing gingivitis and the relationship between brushing teeth and gingivitis. This research was conducted on fifth grade students at Kalanganyar 1 Elementary School in Labuan – Pandeglang District, Banten. In April-May 2022. This research uses cross sectional and quantitative analytical methods with a sample of 47 respondents. The results showed that 39 respondents (83%) had poor criteria for brushing their teeth, 32 respondents (68.1%) had gingivitis and there was a relationship between brushing habits and the incidence of gingivitis based on the Fisher Exact, namely (P - value = 0.009 < 0.05). The conclusion of the relationship brushing habits in class v children with gingivitis in elementary school Kalanganyar 1 Labuan district in 2022, is that there is a relationship between the habit of brushing teeth and the incidence of gingivitis.